Cloning of the A Mating-Type Locus from Lepista nuda and Characterization of Its Genetic Structure - Chengbo Rong; Shuang Zhao; Dengjin Li; Lijuan Wang; Shouxian Wang; Kang Ma; Feng Xu; Yu Liu (Current Microbiology, 2015)

Comparison of SPE, IFE, and FLC in Monitoring Patients with Multiple Myeloma After Autologous Stem Cell Transplantation - Wei Li; Jia-Zi Zhou; Hui-Rong Chang; Li-Jun Dai; Zi-Ling Zhu; Yu-Feng Feng; Fei-Ran Gong; De-Pei Wu (Cell Biochemistry and Biophysics, 2015)

Characteristics of gravity anomalies and prediction of volcanosedimentary boron deposit distribution in the Xiongba area, Tibet - Li-Rong Song; Chang-Qing Yu; Gui-Hua Li; Yang-Yang Feng; Jun-Jie He (Applied Geophysics, 2015)

Psychrobacter fjordensis sp. nov., a psychrotolerant bacterium isolated from an Arctic fjord in Svalbard - Yin-Xin Zeng; Yong Yu; Hui-Rong Li; Wei Luo (Antonie van Leeuwenhoek, 2015)

Seed plant phylogenetic diversity and species richness in conservation planning within a global biodiversity hotspot in eastern Asia - Rong Li; Nathan J.B. Kraft; Haiying Yu; Heng Li (Conservation Biology, 2015)
One of the main goals of conservation biology is to understand the factors shaping variation in biodiversity across the planet. This understanding is critical for conservation planners to be able to develop effective conservation strategies. Although many studies have focused on species richness and the protection of rare and endemic species, less attention has been paid to the protection of the phylogenetic dimension of biodiversity. We explored how phylogenetic diversity, species richness, and phylogenetic community structure vary in seed plant communities along an elevational gradient in a relatively understudied high mountain region, the Dulong Valley, in southeastern Tibet, China. As expected, phylogenetic diversity was well correlated with species richness among the elevational bands and among communities. At the community level, evergreen broad‐leaved forests had the highest levels of species richness and phylogenetic diversity. Using null model analyses, we found evidence of nonrandom phylogenetic structure across the region. Evergreen broad‐leaved forests were phylogenetically overdispersed, whereas other vegetation types tended to be phylogenetically clustered. We suggest that communities with high species richness or overdispersed phylogenetic structure should be a focus for biodiversity conservation within the Dulong Valley because these areas may help maximize the potential of this flora to respond to future global change. In biodiversity hotspots worldwide, we suggest that the phylogenetic structure of a community may serve as a useful measure of phylogenetic diversity in the context of conservation planning.

Isolation, structural analysis, and expression characteristics of the maize TIFY gene family - Zhongbao Zhang; Xianglong Li; Rong Yu; Meng Han; Zhongyi Wu (Molecular Genetics and Genomics, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Purification and Antioxidant Property of Antioxidative Oligopeptide from Short-Necked Clam ( Ruditapes philippinarum ) Hydrolysate In Vitro - Rong Li; Zui-su Yang; Yu Sun; Li Li; Jia-Bin Wang; Guofang Ding (Journal of Aquatic Food Product Technology, 2015)

Osteopontin Mediates Hyperbaric Oxygen Preconditioning-Induced Neuroprotection Against Ischemic Stroke - Sheng-Li Hu; Yu-Xing Huang; Rong Hu; Fei Li; Hua Feng (Molecular Neurobiology, 2015)

Effects of glucose, insulin and triiodothyroxine on leptin and leptin receptor expression and the effects of leptin on activities of enzymes related to glucose metabolism in grass carp (Ctenopharyngodon idella) hepatocytes - Rong-Hua Lu; Yi Zhou; Xiao-Chen Yuan; Xu-Fang Liang; Liu Fang; Xiao-Li Bai; Min Wang; Yu-Hua Zhao (Fish Physiology and Biochemistry, 2015)

Construction of cDNA library from Prunus campanulata leaves and preliminary expressed sequence tag (EST) analysis during cold stress - Ying-Hui Zhang; Jun-Dong Rong; Li-Guang Chen; Ling-Yan Chen; Tian-You He; Yu-Shan Zheng (Biologia, 2015)

Long-term nickel exposure altered the bacterial community composition but not diversity in two contrasting agricultural soils - Jing Li; Hang-Wei Hu; Yi-Bing Ma; Jun-Tao Wang; Yu-Rong Liu; Ji-Zheng He (Environmental Science and Pollution Research, 2015)

The E23K and A190A variations of the KCNJ11 gene are associated with early-onset type 2 diabetes and blood pressure in the Chinese population - Langen Zhuang; Yu Zhao; Weijing Zhao; Ming Li; Ming Yu; Ming Lu; Rong Zhang; Xiaoxu Ge; Taishan Zheng; Can Li; Jun Yin; Jingyuan Yin; et al. (Molecular and Cellular Biochemistry, 2015)

Molecular cloning, characterization and expression of the energy homeostasis-associated gene in piglet - Sheng-ping Wang; Yun-ling Gao; Gang Liu; Dun Deng; Rong-jun Chen; Yu-zhe Zhang; Li-li Li; Qing-qi Wen; Yong-qing Hou; Ze-meng Feng; Zhao-hui Guo (Journal of Zhejiang University-SCIENCE B, 2015)

Different influences of field aging on nickel toxicity to Folsomia candida in two types of soil - Yu-Rong Liu; Jing Li; Ji-Zheng He; Yi-Bing Ma; Yuan-Ming Zheng (Environmental Science and Pollution Research, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

The biological effects of hsa-miR-1908 in human adipocytes - Lei Yang; Chun-mei Shi; Ling Chen; Ling-xia Pang; Guang-feng Xu; Nan Gu; Li-jun Zhu; Xi-rong Guo; Yu-hui Ni; Chen-bo Ji (Molecular Biology Reports, 2015)

Immune protective effect of human alpha-1-antitrypsin gene during β cell transplantation in diabetic mice - Lu Yang; Yu-Ting Liao; Xiao-Fei Yang; Li-Wei Reng; Hui Qi; Fu-Rong Li (Immunologic Research, 2015)

Bacteriological and virulence study of a Mycobacterium chimaera isolate from a patient in China - Guan Liu; Su-Ting Chen; Xia Yu; Yu-Xun Li; Ying Ling; Ling-Ling Dong; Su-Hua Zheng; Hai-Rong Huang (Antonie van Leeuwenhoek, 2015)

Bacterial composition and spatiotemporal variation in sediments of Jiaozhou Bay, China - Xin Liu; Hang-Wei Hu; Yu-Rong Liu; Ke-Qing Xiao; Fan-Sheng Cheng; Ji Li; Tian Xiao (Journal of Soils and Sediments, 2015)

The intracellular carboxyl tail of the PAR-2 receptor controls intracellular signaling and cell death - Zhihui Zhu; Rolf Stricker; Rong yu Li; Gregor Zündorf; Georg Reiser (Cell and Tissue Research, 2015)

Design and applications of bifunctional cinnamide derivatives as potential antimycobacterial agents with few hepatotoxic effects - Zheng-Rong Wu; De-Juan Zhi; Li-Fang Zheng; Jian-Ying Li; Yang Li; Qing-Jian Xie; Na Feng; Yan-Fang Bao; Qi-Yu Gao; Ying Song; Hong-Yu Li (Medicinal Chemistry Research, 2015)